السطات الثلاث في القانون الأساسي لجمهورية ألمانيا الاتحادية - سلمان, إحسان عبدالهادي (Journal of Legal and Political Studies, 2013)
Democracy has been achieved in Germany، as a result of the combined several factors. Was the most important of the existence of basic law suit and the nature of the nation، including the foundations and principles upon which the federal، distributed powers and authorities at the federal and regional levels clearly dedicated to the principle of separation and cooperation between the authorities، and conservative on independence، and has a basic safeguards to protect the rights، freedoms and social justice. The action came the federal and regional authorities، an integral part of the exercise of sovereignty، embodied what put the Basic Law of the key principles to achieve democracy according to the mechanism is not without complexity contributed in establishing the principles of democracy، and succeeded in achieving them.
Keywords: The three authorities; the Basic Law; Germany; Democracy; independence